Synthesis and characterization of transparent hydrophobic sol-gel hard coatings - Wu, Linda Y. L. (2013)
It is challenging to make a transparent hydrophobic hard coating when soft hydrophobic additives are added into the coating system. Material non-homogeneity due to phase separation, non-durable hydrophobicity and deteriorated transparency are the main issues. In this paper, we describe a chemical formulation, which contains a pre-linked hydrophobic cluster and a silica hard matrix with silica hard fillers so that the hydrophobic property and hardness can be tuned separately and optimized. The transparency of the coating is found to be related to the effective modification of the reactive titanium tetraisopropoxide (TIP) precursor by ethyl acetoacetate (EacAc) and the right ratio between TIP and polydimethylsiloxane (PDMS) (≤0.5). The water contact angle is increased to a maximum of 133° when 50 Vol% of PDMS is added into the silica matrix. The hardness of coating is proportional to silica filler content and curing temperature, and inversely proportional to PDMS Vol%. 30 Vol% silica filler in silica matrix and curing temperature at 300°C result in the best hardness in this study. Hardness at 50 Vol% PDMS dropped to 0.2 GPa from 0.85 GPa of pure silica coating. The Vol% of PDMS and silica filler will be further optimized in our next stage experiments.